A STUDY OF OMKAR MEDITATION DESCRIBED IN VEDIC TEXTS - Maurya, Pranshu Kumar; Nidhi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Vedic scriptures, we find a wonderful form of Omkar Sadhana. Sadhaks have praised the glory of Om (Pranav). Pranav is the essence of all Vedas. Indian sages have described this divine sound as Pranav or Om. This word is the first word which is contained in sound and meditation. And its literal meaning is Brahma, this is the root and seed mantra of Indian religion philosophy and spiritual tantra and knowledge. It is supreme from ancient literature to the latest literature. No part of Indian literature is untouched by its dignity and glory. Siddha sadhaks and yogis have also praised its glory. Pronunciation of Om daily not only transmits energy but also helps in keeping away many incurable diseases by increasing the immunity of the body. Om has great importance in spirituality. Many miraculous effects of Om are mentioned in the Vedas. In the modern era, scientists have also confirmed the miraculous effects of Om through research. In western countries, Indian spiritual science, Vedas, Puranas and thousands of years old Indian culture have been the center of research. On the other hand, the source of inspiration for current scientific achievements has been Indian scriptures and Vedas. Yogis believe that it has the power to change the normal consciousness of man. This mantra brings changes in the intellect and body of man. Om brings changes in the body, and mind. Due to which the practitioner becomes healthy. The pronunciation of Om brings purity in the environment.